Sequential Clinical Recovery after Replantation for Complete Finger Amputation in Tamai Zone 1 - Yano, Koichi; Kaneshiro, Yasunori; Hyun, Seungho; Sakanaka, Hideki (Journal of Hand and Microsurgery, 2022)
Background The clinical results of replantation for an amputated distal finger are functionally acceptable. However, few reports exist regarding sequential clinical postoperative recovery. The purpose of this study was to examine the clinical recovery at every 3 months up to 1 year postoperatively.Methods Nineteen patients (16 patients were men), representing 19 fingers with complete amputation at Tamai's zone 1 and replanted successfully, were included in this study. Total active motion (TAM), grip strength (GS), Semmes–Weinstein monofilament (SW) test result, static two-point discrimination (s2PD), and Disability of the Arm, Shoulder, and Hand (DASH) score questionnaire results were obtained postoperatively at 3, 6, 9, and 12 months. Pulp atrophy and nail deformity were assessed at 12 months postoperatively.Results The postoperative %TAM (compared to the uninjured side, 81.8 ± 18.1 at 3 months vs. 91.5 ± 11.9 at 6 months, p < 0.01), %GS (compared with the uninjured side, 61.3 ± 25.9 at 3 months vs. 78.3 ± 20.4 at 6 months, p = 0.02), s2PD (excellent and good/poor; 7/12 at 3 months vs. 18/1 at 6 months, p < 0.01), and DASH scores (26.1 ± 23.1 at 3 months vs. 12.0 ± 12.9 at 6 months, p < 0.01) recovered significantly from 3 to 6 months but did not change significantly from 6 months onward. The SW test results showed a significant recovery between 3 and 12 months postoperatively (2.83 and 3.61/4.31, 6.65, and undetectable, 1/18 at 3 months vs. 7/12 at 12 months, p = 0.04). The DASH score at 12 months postoperatively was significantly associated with %TAM (r = −0.64, p < 0.01) and %GS (r = −0.58, p < 0.01) at 12 months postoperatively and age (r = 0.52, p = 0.02). Five fingers had pulp atrophy and four fingers had nail deformity.Conclusion This 1-year follow-up study showed the sequential clinical recovery after replantation for complete amputation in Tamai zone 1. Postoperative %TAM, %GS, and the DASH score recovered significantly between 3 and 6 months but significant recovery up to 1 year was not observed.
Keywords: finger amputation; replantation; zone 1; clinical recovery